AT1 receptor blockade alters nutritional and biometric development in obesity-resistant and obesity-prone rats submitted to a high fat diet - Smith, Pauline M.; Hindmarch, Charles C. T.; Murphy, David; Ferguson, Alastair V. (Frontiers in Psychology, 2014)
Obesity is a chronic metabolic condition with important public health implications associated with numerous co-morbidities including cardiovascular disease, insulin resistance, and hypertension. The renin angiotensin system (RAS), best known for its involvement in cardiovascular control and body fluid homeostasis has, more recently, been implicated in regulation of energy balance. Interference with the RAS (genetically or pharmacologically) has been shown to influence body weight gain. In this study we investigated the effects of systemic AT1 receptor blockade using losartan on ingestive behaviors and weight gain in diet induced obese (DIO) rats. Prior to losartan administration (30mg/kg/day) body weight gain remained constant within the DIO animals (3.6 ± 0.3g/day, n=8), diet resistant (DR) animals (2.1 ± 0.6g/day, n=8) and in the age matched chow fed control (CHOW) animals (2.8 ± 0.3g/day, n=8), Losartan administration abolished body weight gain in animals fed a high fat diet (DIO: -0.4 ± 0.7g/day, n=8; and DR: -0.8 ± 0.3g/day, n=8) while chow fed animals continued to gain weight (2.2 ± 0.3g/day, n=8) as they had previously to oral administration of losartan. This decrease in daily body weight gain was accompanied by a decrease in food intake in the high fat diet fed animals. Following the removal of losartan, both the DIO and DR animals again showed daily increases in body weight gain and food intake which were similar to control values. Our data demonstrate that oral losartan administration attenuates body weight gain in animals fed a HFD whether the animal is obese (DIO) or not (DR) while having no effect on body weight gain in age matched chow fed animals suggesting a protective effect of losartan against body weight gain while on a HFD.